Between two skies - O'Sullivan, Joanne (Candlewick Press, 2019)
In Bayou Perdu, Louisiana, lives sixteen-year-old Evangeline Riley, a girl who holds two titles in the under-sixteen fishing rodeo and loves nothing more than being on her skiff between the bayou water and the open sky. Her peaceful life is totally changed by Hurricane Katrina. Chaos tears her world apart, but it also causes her to meet Tru, an attractive boy her age. However, love is hard to develop when neither of them seems to have a home anymore.